Pengaruh Nilai Etis Perusahaan, Kepemimpinan Etis, dan Kebahagiaan terhadap Kinerja Karyawan - R. Iqbal Robbie; Kenny Roz (Penerbit Goodwood, 2025)
Purpose: The purpose of this study is to determine the effect of corporate ethical values and ethical leadership on employee performance through happiness at work at the Saiful Anwar Hospital Malang. Research Methodology: This research uses a quantitative approach. The sample used was that all employees who worked at Saiful Anwar Regional Hospital were 148 respondents. Data collection techniques through interview and questionnaire. Data Analysis Method Using Scale Range Analysis and Data Processing Using Smart PLS Software Program Version 4.0. Results: The results of this study are the value of corporate ethics have a negative and insignificant effect on employee performance, corporate ethical values have a positive and significant effect on happiness at work, ethical leadership has a positive and significant effect on employee performance, ethical leadership has a negative and not significant effect on happiness at work, happiness at work has a positive and significant effect on employee performance Conclusion: The study finds that corporate ethical values enhance employee performance through full mediation of happiness at work, while ethical leadership directly improves performance but shows no indirect effect through happiness at work. Limitations: The questionnaire was not filled in completely by all respondent. Contribution: It is expected that the results of this study can be a reference for further researchers and add insight in explaining the relationship between corporate ethical values, ethical leadership and happiness in the workplace on employee performance). In addition, the results of this study are expected to be a consideration for management in decision making and implementing policies.